Divorce Lawsuit Due to Impotence Perspective Maslahat Theory: Case study of the Andoolo Religious Court Decision, Southeast Sulawesi - Fitri, Atika; Bahar, Muchlis; Azwar, Zainal; Ediz, M. Hidayat; Yusrial, Yusrial (El-Usrah: Jurnal Hukum Keluarga, 2024)
This research aims to analyze the decision to sue for divorce because the husband is impotent from the perspective of maslahat theory. The main condition for building a harmonious family is the existence of mutual trust and understanding between husband and wife. However, in living a married life, problems sometimes arise, such as the husband suffering from impotence, which can disrupt the relationship between husband and wife. This type of research is normative legal research, the data source is secondary data in the form of the decision of the Andoolo Religious Court, Southeast Sulawesi, Number 0225/Pdt.G/2019/PA.Adl regarding divorce due to husband suffering from impotence. This research found that the judge's consideration in deciding case Number 0225/Pdt.G/2019/PA.Adl was that the judge granted the divorce suit on the grounds that there had been continuous disputes and quarrels between husband and wife, the factor causing the disputes and quarrels was that the defendant was unable to produce children. The defendant suffered from impotence which the plaintiff only discovered after marrying the defendant. The judge's considerations were in accordance with the provisions of Article 19 letter (f) Government Regulation Number 9 of 1975 concerning the Implementation of Law Number 1 of 1974 concerning Marriage jo. Article 116 letter (f) KHI, so that the Plaintiff's divorce claim is granted. The judge's considerations in granting the divorce suit are also in accordance with the benefit theory, including benefits for the wife, benefits for the husband and benefits for society.